Labor discrimination by gender in the tourism sector: An analysis for the Peruvian case in the context of COVID-19 - Del Pozo Loayza, Cesar Edinho (2023)
This article identifies processes of gender-based labor discrimination in the Peruvian tourism sector. We analyze the determinants of the gender wage gap between men and women in the context of the COVID-19 pandemic. We use the National Household Survey from 2018 to 2021 and the methodology of decomposing wage gaps by quantiles proposed by Machado and Mata (2005), which includes a correction for selection bias in the labor participation of men and women in the tourism sector (Buckinsky, 1998; Albrech et al., 2009). The wage gap was decomposed into differences in job characteristics (education, experience) and differences in the returns to such characteristics. The results show that the wage gap is unfavorable to women and is mainly explained by differences in returns, particularly in the lower quantiles of the wage distribution. Labor discrimination processes against women in tourism would have increased during the pandemic, particularly the sticky floor effect.